Synthesis, and studying effect of a solvent on the 1H-NMR chemical shifts of 4-Azido-N-(6-chloro-3-pyridazinyl)benzenesulfonamide - Hasan, sadiq (Al-Qadisiyah Journal of Pure Science, 2021)
The compound 4-Azido-N-(6-chloro-3-pyridazinyl)benzenesulfonamide was synthesized and studied using FTIR, and 1H-NMR . The influence of a solvent on the experimental 1H-NMR chemical shifts of title compound is discussed. Small chemical shift Δδ < 0.1 ppm were observed when switching from DMSO-d6 to CD3OD. Record a marked change in chemical shifts valeues Δδ > 0.3 ppm when transform from high-polar solvents (DMSO-d6,and CD3OD) to low-polar solvent (CDCl3). The 1H-NMR chemical shifts of C2-H and C6-H were shown to have excellent linear correlation with the dielectric constants of the solvents DMSO-d6, CD3OD,and CDCl3 (r = 0.995). The 1H-NMR chemical shifts of C18-H shows a perfect relationship with solvatochromic parameter β (r = 0.999).